Mathematical formulation of multicomponent composites wear forecasting in the zone of friction - Скачков, Віктор Олексійович; Іванов, Віктор Ілліч; Воденніков, Сергій Анатолійович; Сергієнко, Сергій Сергійович (Eastern-European Journal of Enterprise Technologies, 2012)
Mathematical formulation for process of the wear multicomponent composites in the zone of friction is offered. It is experimentally researched the mass wear of structurally-heterogeneous alloy on the basis of calcium babbit and graphite with protective-consolidating coverage